2009
DOI: 10.1090/s0002-9947-09-04575-9
|View full text |Cite
|
Sign up to set email alerts
|

Commutator maps, measure preservation, and 𝑇-systems

Abstract: Abstract. Let G be a finite simple group. We show that the commutator map α : G × G → G is almost equidistributed as |G| → ∞. This somewhat surprising result has many applications. It shows that a for a subset X ⊆ G we have α −1 (X)/|G| 2 = |X|/|G| + o(1), namely α is almost measure preserving. From this we deduce that almost all elements g ∈ G can be expressed as commutators g = [x, y] where x, y generate G.This enables us to solve some open problems regarding T -systems and the Product Replacement Algorithm … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 32 publications
0
55
0
Order By: Relevance
“…This result is new even for k = 2; in fact, it is likely that the word x 2 1 x 2 2 is surjective on all finite simple groups of order > 2 (see [GS09] for related results). Finally, our methods may be relevant to a well-known conjecture of J. G. Thompson, stating that any finite simple group Γ has a conjugacy class C such that C 2 = Γ.…”
mentioning
confidence: 94%
“…This result is new even for k = 2; in fact, it is likely that the word x 2 1 x 2 2 is surjective on all finite simple groups of order > 2 (see [GS09] for related results). Finally, our methods may be relevant to a well-known conjecture of J. G. Thompson, stating that any finite simple group Γ has a conjugacy class C such that C 2 = Γ.…”
mentioning
confidence: 94%
“…This implies that every element of a large finite simple group is a product of two commutators. In [19] it is shown that the commutator map on finite simple groups is almost measure-preserving, a result having applications to the product replacement algorithm [7].…”
Section: Introductionmentioning
confidence: 99%
“…Note that we cannot require in this theorem that S = G. Indeed, it is well known (and follows from (19) Two proofs are given in [41] for this theorem. The first is probabilistic whereas in the second the subsets S are explicitly constructed.…”
Section: Theorem 522 ([41 Theorem 15])mentioning
confidence: 98%
“…Yet another type of problems, first introduced in [41], arises when one asks about the behaviour of the fibres of the word map rather than about its image. Namely, Shalev asked [113, Problem 2.10] whether (the cardinalities of) these fibres are equidistributed (or close to be equidistributed) when varies in some "large" subset of the image of and G runs over some family of finite groups.…”
Section: ∈ G} As the Set Of Values Of In Gmentioning
confidence: 99%
See 1 more Smart Citation